Eficiência de herbicidas pré e pós-emergentes no controle de azevém e aveia preta na cultura do trigo - Kamphorst, Vinicius Boaro (2023)
Ryegrass (Lolium multiflorum) and black oat (Avena strigosa) are the main weeds in wheat (Triticum aestivum). Given this scenario, the study aimed to evaluate the efficiency of the use of pre- and post-emergent herbicides, isolated and intercropped. The experimental design was randomized blocks, with 10 treatments and 3 repetitions, totaling 30 experimental units. The treatments consisted of a control (without weed control), weeding management with 100% control and isolated herbicides (preemergent: Piroxasulfone and Trifluralin, and post-emergent: Piroxsulam and Clodinafope-Propargil) and in combination of pre + post-emergents (Piroxasulfone + Clodinafop-Propargil and Piroxsulam + Piroxsulam; Trifluralin + Clodinafop-Propargil and Trifluralin + Piroxsulam). The use of pre-emergent herbicides Pyroxasulfone and Trifluralin was effective in the initial control of ryegrass and black oats, maintaining a population (m²) at 28 DAA of 16 and 9 and 4 and 4 plants (m²) respectively of ryegrass and black oats, highlighting the treatment with Trifluralin, which provided the lowest population index (m²) of ryegrass and black oats and the highest wheat yield (2,900 kg ha-1). Regarding wheat productivity, the treatment with manual weeding produced 1,591 kg ha-1 more than the treatment without weed control. The post-emergence treatments, Clodinafop-Propargil and Piroxsulam, demonstrated better weed control and resulted in higher yields (3,473 and 3,200 kg ha-1 respectively) compared to the isolated treatment with Piroxasulfone and Trifluralin (2,724 and 2,900 kg ha-1 respectively). The associated use of pre- and post-emergence herbicides was found to be good allies for population control of ryegrass and black oat plants, resulting in the best average yields (Trifluralin + Piroxsulam = 3,466 kg ha-1; Piroxasulfone + Piroxsulam = 3,509 kg ha-1; Pyroxasulfone + Clodinafop-Propargil = 3,617 kg ha-1; Trifluralin + Clodinafop-Propargil = 3,869 kg ha-1), achieving the productivity of the plot with total control of the respective weeds (Weeding = 3,800 kg ha-1). The treatment with Clodinafop-Propargil + Trifluralin stands out, which had the best function in weed population control and better final productivity.